Process Modeling, Optimization and Characterization of Silicon <100> Optical Waveguides by Anisotropic Wet Etching - Haroon, Hazura; Hanim, Abdul Razak; Mardiana, Bidin; Sahbudin, Saari; Menon, P.S (Trans Tech Publications, 2012)
We present a detailed fabrication process of silicon optical waveguide with a depth of 4μm via simulation and experiment. An anisotropic wet etching using Potassium Hydroxide (KOH) solutions was selected to study the influence of major fabrication parameters such as etch rate, oxidation time and development time to the fabrication performance. The fabrication of the silicon waveguide with the orientation of <100> was modeled using ATHENA from 2D Silvaco software and was later compared with the actual fabricated device. Etching time of 4 minutes was required to etch the Si to the depth of 4μm to obtain a perfectly trapeizoidal optical waveguide structure. Our results show that the simulation model is trustworthy to predict the performance of the practical anisotropic wet etching fabrication process. The silicon-based waveguide components are targeted to be employed in realizing future photonic devices such as optical modulators.